Bacillus anthracis genomic DNA enhances lethal toxin–induced cytotoxicity through TNF-α production - Jeon, Jun Ho (BMC Microbiol, 2014)
BACKGROUND: Bacillus anthracis is the etiological agent of anthrax. Lethal toxin (LT) produced by B. anthracis is a well-known key virulence factor for anthrax because of its strong cytotoxic activity. However, little is known about the role of B. anthracis genomic DNA (BAG) in anthrax pathogenesis. RESULTS: We examined the effect of BAG on TNF-α production and LT-mediated cytotoxicity during B. anthracis spore infection in mouse macrophage cell lines (RAW264.7 cells and J774A.1) and BALB/c mice. Infection of RAW264.7 cells with B. anthracis spores induced TNF-α expression in a multiplicity of infection (MOI)-dependent manner, and this enhancement was attenuated by the toll-like receptor (TLR) 9 inhibitor oligodeoxynucleotide (ODN)2088. BAG led to TNF-α expression in a dose- and time-dependent manner when applied to RAW264.7 cells. TNF-α expression induced by BAG was reduced by either pretreatment with TLR9 inhibitors (ODN2088 and chloroquine (CQ)) or transfection with TLR9 siRNA. Furthermore, BAG-induced TNF-α production in TLR9(+/+) macrophages was completely abrogated in TLR9(−/−) macrophages. BAG enhanced the phosphorylation of mitogen-activated protein kinases (MAPK), and BAG-induced TNF-α expression was attenuated by pretreatment with MAPK inhibitors. A reporter gene assay and confocal microscopy demonstrated that BAG increased NF-κB activation, which is responsible for TNF-α expression. Treatment with BAG alone showed no cytotoxic activity on the macrophage cell line J774A.1, whereas LT-mediated cytotoxicity was enhanced by treatment with BAG or TNF-α. Enhanced LT-induced lethality was also confirmed by BAG administration in mice. Furthermore, LT plus BAG-mediated lethality was significantly recovered by administration of Infliximab, an anti-TNF-α monoclonal antibody. CONCLUSIONS: Our results suggest that B. anthracis DNA may contribute to anthrax pathogenesis by enhancing LT activity via TLR9-mediated TNF-α production. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-014-0300-9) contains supplementary material, which is available to authorized users.